Bloomberg's New York : class and governance in the luxury city - Brash, Julian (Geographies of justice and social transformation ;, 2011)
New York mayor Michael Bloomberg claims to run the city like a business. In Bloomberg's New York, Julian Brash applies methods from anthropology, geography, and other social science disciplines to examine what that means. He describes the mayor's attitude toward governance as the Bloomberg Way-a philosophy that holds up the mayor as CEO, government as a private corporation, desirable residents and businesses as customers and clients, and the city itself as a product to be branded and marketed as a luxury good. Commonly represented as pragmatic and nonideological, the Bloomberg Way, Brash argues, is in fact an ambitious reformulation of neoliberal governance that advances specific class interests. He considers the implications of this in a blow-by-blow account of the debate over the Hudson Yards plan, which aimed to transform Manhattan's far west side into the city's next great high-end district. Bringing this plan to fruition proved surprisingly difficult as activists and entrenched interests pushed back against the Bloomberg administration, suggesting that despite Bloomberg's success in redrawing the rules of urban governance, older political arrangements-and opportunities for social justice-remain.